INFLUENCE OF ZINGIBER ZERUMBET EXTRACTS AS FEED ADDITIVE ON PERFORMANCE, CARCASS CHARACTERISTICS AND INHIBITION OF ESCHERICHIA COLI BACTERIA OF COMMERCIAL BROILER CHICKENS - Rafiqi, Rojaur; Ryanda, M. Afzalul; Fuadi, M. Afid; Riwa, Nanda; Wahyudi, Indra; Ilham, Ilham; Allaily, Allaily; Wajizah, Sitti; Samadi, Samadi (Jurnal Kedokteran Hewan, 2022)
The purpose of this study was to evaluate administration of Zingiber zerumbet (Z. zerumbet) extracts on performances, carcass characteristics and Echerichia coli (E. coli) bacteria of commercial broiler chickens. One hundred day old CP 707 broiler chickens (mixed sex) were randomly distributed into 20 floor pens with four treatments and five replicates. Each group of broilers was treated with diffrent level of Z. zerumbet extracts in drinking water (P0= control, P1= 0.025 % in drinking water, P2= 0.050 % in drinking water and P3= 0.075 % in drinking water). Broiler chickens were fed commercial diet based on nutrition requirement for starter and grower. Feed and water were provided ad libitum. Body wright of chickens and feed were recorded weekly. All data were recorded to measure for performances, carcass characteristics and the inhibition of E. coli bacteria. The data were analyzed by one-way ANOVA. Statistically differences among treatments were stated with a probablity of P0.05. The results of study indicated that administration of Z. zerumbet extract in drinking water with different concentration up to 4 weeks did not significantly influence (P0.05) on the performances, carcass and giblet characteristics of broiler chickens. The inhibition of E. coli bacteria was significantly affected (P0.05) by inclusion of Z. zerumbet at different concentration. In conclusion, administration of Z. zerumbet in drinking diet had no detrimental effect on animal performance, carcass and giblet characteristics.